2021
DOI: 10.1088/1742-6596/1808/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Natural Fiber Reinforced Polymer in Automotive Application: A Systematic Literature Review

Abstract: Efforts to develop effective and innovative materials are increasingly being developed by researchers, especially in the development and utilization of NFRP (Natural Fiber Reinforced Polymer) in the automotive sector due to increased demand and increased ecological awareness. The purpose of this literature review article is to provide up-to-date information on the application of NFRP and plastic recycling in the automotive sector as well as consideration of selecting natural fibers for use as reinforcing compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Therefore, it is recommended to investigate different parameters that could improve the printing quality and influence the printed NFRCs’ mechanical performance, such as processing temperatures, layer orientation, deposition speed, infill pattern, and layer thickness [ 80 ]. Furthermore, our results warrant further research of NFRCs made of printed PLA reinforced with natural henequen fibers for construction and automotive applications [ 16 , 81 ]. These studies should include strategies to improve fiber–matrix adhesion and reduce fiber agglomeration during the filament extrusion process and defects during the printing process.…”
Section: Resultsmentioning
confidence: 66%
“…Therefore, it is recommended to investigate different parameters that could improve the printing quality and influence the printed NFRCs’ mechanical performance, such as processing temperatures, layer orientation, deposition speed, infill pattern, and layer thickness [ 80 ]. Furthermore, our results warrant further research of NFRCs made of printed PLA reinforced with natural henequen fibers for construction and automotive applications [ 16 , 81 ]. These studies should include strategies to improve fiber–matrix adhesion and reduce fiber agglomeration during the filament extrusion process and defects during the printing process.…”
Section: Resultsmentioning
confidence: 66%
“…Abaca fibers, due to its nature buoyancy, resistance to salt water damage, and low swelling, are primarily used in marine ropes but also finds used within interior components of vehicles. 43,46,47 Perhaps most environmentally impactful is their use as a replacement for asbestos in vehicle friction brakes. 48 Paglicawan et al reported that plasma-treatment of abaca fabric in an epoxy matrix was required for sufficient matrix-fiber cohesion.…”
Section: Leaf Fibersmentioning
confidence: 99%
“…The proportion of bioplastics produced for packaging in 2020 was 47%, 11 only slightly higher than 40% for conventional plastics. 131 Myth: The production of bio-based polymers takes up much agricultural land and impacts human and animal food production.…”
Section: Challenges Of Bio-based Polymersmentioning
confidence: 99%